The Influence of Celebrity Endorsers and Discounts on Impulse Buying Moderated by Hedonic Shopping Motivation in Generation Z Online - Rosdiana; Abdurrahman (Formosa Journal of Sustainable Research, 2023)
In line with the development of technology, it is currently able to change one's behavior in shopping online. The purpose of this study was to determine the effect of celebrity endorsers and price discounts on impulse buying which is moderated by hedonic shopping motivation. The sample collection technique uses purposive sampling method. Data collection was carried out by distributing questionnaires online with a total of 150 respondents. The data analysis tool used is moderated regression analysis (MRA). The findings from this study are celebrity endorsers have no effect on impulse buying, price discounts have a positive effect on impulse buying, hedonic shopping motivation does not moderate the relationship between celebrity endorsers on impulse buying, and hedonic shopping motivation moderates the relationship between price discounts on impulse buying